Design and Hydrodynamic Experiment Research on Novel Biomimetic Pectoral Fins of a Ray-Inspired Robotic Fish - Lingkun Chen; Shusheng Bi; Yueri Cai; Hongcheng Qiu (Machines, 2022)
Bionic propulsion has certain advantages over traditional propellers. Much research on pectoral fins as bionic propellers for ray-inspired robots has been made, but rarely did they compare the hydrodynamic performance of different fins on the same platform to find out optimal balance. In this paper, the existing prototypes are categorized into three structure types, and a new bionic pectoral fin module used on a ray-inspired robotic fish was presented, together with a novel 2-DOF spatial parallel mechanism as the bionic propeller. Motion analysis of the mechanism agreed well with the pectoral fin kinematic model, providing a reliable basis to test different types of fins. Design and fabrication of the new bionic fin module as well as two traditional ones are also explained. Hydrodynamic experiment was conducted to study the differences between each fin type under various working conditions. Results indicate that the thrust generated by the fin oscillation is closely related to four parameters (amplitude, frequency, phase difference, and flow velocity), and there are optimal value ranges for better propelling performance when the frequency is around 0.5 Hz and phase difference is near 30°. Thanks to better profile preservation and hydro force interaction, the newly proposed pectoral fins had higher performance than the traditional ones in terms of thrust generation and controllability when the amplitude is higher than 30° and frequency is over 0.3 Hz. An average thrust of 2.98 N was recorded for the new fin module at the max amplitude of 60°, 11.6% and 16.4% higher than the other two comparative test groups, respectively.